Disparitas Penerapan Sanksi Pidana Dalam Putusan Pengadilan Terhadap Kasus Tindak Pidana Korupsi - Satriana, I Made Wahyu Chandra; Ni Made Liana Dewi; I Nyoman Vaisa Budi Viratama (Jurusan Hukum Fakultas Dharma Duta Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Disparity does not only occur in the same criminal act, but also in the level of seriousness of a criminal act, and also in the judge's decision, either by one panel of judges or by different panels of judges for the same case. Of course, the reality regarding the scope of this growing disparity has given rise to inconsistencies in the judicial environment. The problem of this research is what causes disparities in the application of criminal sanctions to the same case for perpetrators of criminal acts of corruption and how best to ensure that in the future there will no longer be disparities in court decisions on the same cases for perpetrators who are not criminally corrupt. This type of thesis research uses empirical legal research. The results of this research are the causes of disparities in the application of criminal sanctions to the same case for perpetrators of criminal acts of corruption: (a). The legal factor is that the provisions in Law Number 20 of 2001 do not recognize a specific minimum sentence, so that determining the severity of the sentence imposed is left entirely up to the judge. (b) The judge factor, in the event that the case examination is split into several files (splitting) where the case has the same characteristics and characteristics starting from the indictment, prosecution, examination of evidence and witnesses, then the consequence is that each file is examined by a different Panel of Judges. . So that in the future there will no longer be disparities in court decisions, every criminal sentence must be carried out by paying attention to the certainty and proportionality of punishment to realize justice based on Pancasila and the 1945 Constitution of the Republic of Indonesia.